2015
DOI: 10.1155/2015/823835
|View full text |Cite
|
Sign up to set email alerts
|

Yield of Screening Colonoscopy in Renal Transplant Candidates

Abstract: In a population of asymptomatic potential kidney transplant recipients ≥50 years of age, the prevalence of colorectal adenomatous polyps was 24%. Colonoscopy appeared to be useful as a screening tool in potential transplant recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
1
4
1
Order By: Relevance
“…We found an overall adenoma detection rate of 18.1% of the patients who underwent endoscopy within the pre-transplant work-up. These results correspond to results in the literature for the general population, as well as the ESRD population [ 36 , 48 50 ]. The studied population of patients with ESRD is a subgroup that actually received a kidney graft.…”
Section: Discussionsupporting
confidence: 90%
“…We found an overall adenoma detection rate of 18.1% of the patients who underwent endoscopy within the pre-transplant work-up. These results correspond to results in the literature for the general population, as well as the ESRD population [ 36 , 48 50 ]. The studied population of patients with ESRD is a subgroup that actually received a kidney graft.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, the prevalence of overall adenoma, advanced adenoma, and CRC among the pretransplant ESRD patients was 35.4%, 8.1%, and 0.2%, respectively. The rate of adenoma detection via colonoscopy among pretransplant ESRD patients in our study (35.4%) is higher than most reported adenoma detection rates for the general population, although there are other recent reports [23][24][25][26] of higher rates of adenomatous polyps in chronic kidney disease and ESRD patients that vary from 24% to 54%. Furthermore, the risk of CRC appears higher in solid-organ transplant patients than in the general population.…”
Section: Discussioncontrasting
confidence: 86%
“…This study about the results of screening colonoscopy in a cohort of 169 renal transplant candidates over 50 years old showed a prevalence of colorectal polyps of 24%, 4 advanced adenomas, and 1 adenocarcinoma. The authors conclude that colorectal cancer screening is indicated in renal transplant candidates over 50 years old and that the choice of the screening test should be individualized based on patient's preference and risk benefit ratio [ 1 ].…”
mentioning
confidence: 99%